Improving food systems for healthy diets and nutrition in Nigeria: Policies and actions - Onilogbo, Omobolanle Nuratu (CGIAR System Organization, 2024)
On July 25, 2024, the International Food Policy Research Institute (IFPRI) and the Global Alliance for Improved Nutrition (GAIN) co-organized the launch of IFPRI’s 2024 Global Food Policy Report (GFPR) titled “Food Systems for Healthy Diets and Nutrition” in Nigeria with the support of the CGIAR Initiative on National Policies and Strategies. The event theme was “Improving Food Systems for Healthy Diets and Nutrition in Nigeria: Policies and Actions”. The event drew together various stakeholders in the agricultural policy space and reflected on the report’s relevance for diverse issues confronting Nigeria in the areas of food security and healthy diets.